(untitled) (Journal of Mathematics Mechanics and Computer Science, 2019)
In this paper, we consider the dynamics of a large-scale cloud formed in strong explosions in an inhomogeneous atmosphere, with allowance for turbulent mixing and adiabatic expansion. Numerical simulation is carried out on the basis of the solution of the three-dimensional filtered non-stationary Navier-Stokes equation, the continuity equation, the concentration equation, the enthalpy equation, and the equation of state for compressible media. The modified solver is based on the OpenFOAM mathematical physics library. To close the basic equations, a viscous model of turbulence is used. The change in the size of the cloud in the atmosphere is determined depending on the thermodynamic parameters. The calculation of the explosion energy calculated for the remainder of the Proton-M carrier rocket was made.